2019
DOI: 10.1111/cod.13263
|View full text |Cite
|
Sign up to set email alerts
|

Myroxylon pereiraeresin (balsam of Peru) – A critical review of the literature and assessment of the significance of positive patch test reactions and the usefulness of restrictive diets

Abstract: In this article, contact allergy to Myroxylon pereirae resin (MP) (balsam of Peru) is reviewed. The topics presented include the uses, the chemical composition, the frequency of sensitization, the relevance of positive reactions, the MP-containing products causing allergic contact dermatitis, co-reactivity with other fragrance and nonfragrance materials, the sensitizers, the usefulness of MP as a "marker" of fragrance allergy, and the effectiveness of, and indications for, "balsam-restrictive" diets. Sensitiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 158 publications
2
45
1
2
Order By: Relevance
“…The age gradient of positive reactions to M. pereirae (balsam of Peru) is even more marked than that of FM I. This “ill‐defined natural fragrance mix” is an apparently important, but also enigmatic allergen, concerning the consequences of a positive patch test for the patient, as recently reviewed by de Groot 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age gradient of positive reactions to M. pereirae (balsam of Peru) is even more marked than that of FM I. This “ill‐defined natural fragrance mix” is an apparently important, but also enigmatic allergen, concerning the consequences of a positive patch test for the patient, as recently reviewed by de Groot 35 …”
Section: Discussionmentioning
confidence: 99%
“…This "ill-defined natural fragrance mix" is an apparently important, but also enigmatic allergen, concerning the consequences of a positive patch test for the patient, as recently reviewed by de Groot. 35 The dramatic increase of contact allergy prevalence to MI and, parallel to this, to the mixture methylchloroisothiazolinone (MCI)/MI 3:1 in the recent past, and the decline since 2013/2014 have been repeatedly reported and discussed, 9,36 and shall not be expanded on here. The fact that MI 0.02 and 0.05% aq.…”
Section: European Baseline Series (Version 2015)mentioning
confidence: 99%
“…A recent review of the chemistry and epidemiology of MPR has demonstrated that traditional sources of exposure and sensitization have now vanished in most countries. 29 Therefore, the clinical relevance of MPR contact allergy is notoriously difficult to explain, particularly to the sensitized patient. As only a small proportion of patients positive to FM I are, at the same time, positive to SSO, the prevalence estimate for FM I contact allergy is hardly affected by considering SSO or not.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for fragrance substance contact allergy in routine patch testing is achieved by the use of two fragrance mixes (I and II), including 8 and 5 single constituents, respectively. Furthermore, a natural mixture, Myroxylon pereirae resin, is routinely tested, containing a number of constituents to which exposure is also possible independent of this mixture, while other constituents are more characteristic for Myroxylon pereirae, and some constituents are shared with propolis (see under "woods, plants and plant products" below), as recently reviewed [65]. It has repeatedly been found that using these screening markers, only about half of all fragrance-allergic patients are diagnosed; hence some departments routinely test with all 26 fragrances currently needing to be labelled in the EU according to Annex III of EU Cosmetic Regulation 1223/2009 [66].…”
Section: Fragrancesmentioning
confidence: 99%